Search 78,064 tutors
FIND TUTORS
Ask a question
0 0

Functions please help

Tutors, please sign in to answer this question.

1 Answer

f(x ) = 3X^2 - 5X + 9      g(x) = 1 - 4x
 
a) (  f - g ) ( x ) = 3X^2 - 5X + 9 - ( 1 - 4x ) =
 
                        =  3 X^2 - 5X + 9 -1 + 4X
                     
                         = 3 X^2 - X + 8
 
b)
      ( f ° g ) (x) = 3 ( 1 -4x ) ^2 - 5 ( 1 - 4X) + 9
 
                        =  3 ( 1 - 8X + 16 X^2 ) - 5 + 20X + 9
 
                         = 48 X^2 - 4X +7